KABUPATEN CILACAP MENUJU SMARTCITY: PENERIMAAN GEN Z-MILLENIAL DALAM VISI CILACAP SMART REGENCY - Alfarizi, Muhammad; Arifian, Rafialdo (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2023)
The development of Cilacap Smart City must consider the needs of its population, even though generally, districts and cities adopt similar Smart City systems. Cilacap is striving to develop Cilacap Smart City with a focus on achieving a balance between urban and rural areas. However, there has been no research on how rural communities, deeply rooted in cultural traditions and local wisdom, respond to this concept. This study aims to uncover the acceptance of the millennial and Gen Z generations in Cilacap towards Smart City, particularly the Cilacap Smart Regency program. In this research, the